ER−/PR+/HER2− breast cancer type shows the highest proliferative activity among all other combined phenotypes and is more common in young patients: Experience with 6643 breast cancer cases. Issue 3 (27th March 2019) - Arena, Vincenzo; Pennacchia, Ilaria; Vecchio, Fabio M.; Carbone, Arnaldo
Abstract: The characterization of breast cancer according to its proliferative activity and the expression of estrogen receptors, progesterone receptors, and human epidermal growth factor receptor‐2 is a laboratory routine that has been adopted worldwide for prognostic and therapeutic purposes. By combining data on the expression of estrogen receptors, progesterone receptors, and human epidermal growth factor receptor‐2, it is possible to obtain 8 tumor patterns categorized as triple‐negative, nonluminal (i.e. positive for human epidermal growth factor receptor‐2 with four subtypes) and luminal (negative for human epidermal growth factor receptor‐2 and positive for estrogen receptor and/or progesterone receptor with three subtypes) tumors. In general, luminal tumors are associated with a higher degree of tumor differentiation and have more favorable clinical outcomes. One of the subtypes of luminal tumors has an ER−/PR+ profile. This is a rather rare tumor subtype that behaves aggressively. The aim of this work was to analyse the proliferative activity of the eight tumor subgroups to verify if the ER−/PR+ type has a higher proliferative activity than the other subtypes, which might be correlated with its more aggressive behavior. To accomplish this, we examined estrogen receptor, progesterone receptor, human epidermal growth factor receptor‐2 and Ki67 data from 6643 cases of breast cancer. We found that the tumor type that was positive for only the progesterone receptor and negative for both the estrogen receptor and human epidermal growth factor receptor‐2 (1.3% of all cases) had a proliferative activity that was consistently much higher than those of the other luminal subtypes.